An integrated poultry, multi-species aquaculture for Malaysian rice farmers: a mixed integer programming approach - Kadir Alsagoff, Syed A.; Clonts, Howard A.; Jolly, Curtis M. (Elsevier, 1990)
Integrated Aquaculture Farming (IAF) offers hope for increasing income significantly for poor Malaysian subsistence farmers. Poverty among Malaysian farmers is widespread. Ninety per cent of rice farmers earn less than M$160 per month to support an average family composed of 5·5 members. A 2·0 ha wet-rice farm integrated with poultry and multi-species aquaculture was developed from Malaysian farm and agriculture data to study IAF viability. The IAF design particularly addressed aquacultural problems in poultry integration, especially in the area of synchronizing broiler and fish growth cycles for organic fertilization of fish ponds. A mixed integer linear program (MIP) was utilized for the analysis. The results indicated that the feasibility of IAF was marginal in the absence of governmental assistance in the form of grants or interest free loans for pond construction. The MIP analyses determined Macrobrachium polycultured with Chinese carp optimized farmer returns.